Diet in the management of type 2 diabetes: umbrella review of systematic reviews with meta-analyses of randomised controlled trials - Lukas Schwingshackl; Sabrina Schlesinger; Janett Barbaresko; Anna Stahl-Pehe; Edyta Szczerba; Tim Schiemann (BMJ Medicine)
Objective To systematically summarise and evaluate the existing evidence on the effect of diet on the management of type 2 diabetes and prevention of complications.Design Umbrella review of systematic reviews with meta-analyses of randomised controlled trials.Data sources PubMed, Embase, Epistemonikos, and Cochrane, from inception up to 5 June 2022.Eligibility criteria for selecting studies Systematic reviews with meta-analyses of randomised controlled trials reporting summary effect estimates on the effect of diet on any health outcome in populations with type 2 diabetes were included in the review. Only meta-analyses with randomised controlled trials with the duration of at least 12 weeks were eligible for inclusion. Summary data were extracted by two investigators independently. Summary effect estimates with 95% confidence intervals were recalculated with a random effects model if the information provided was insufficient. Methodological quality was assessed with the A MeaSurement Tool to Assess systematic Reviews (AMSTAR) 2 tool and the certainty of evidence with the Grading of Recommendations Assessment, Development, and Evaluations (GRADE) approach.Results 88 publications with 312 meta-analyses of randomised controlled trials were included. Methodological quality was high to moderate in 23% and low to very low in 77% of the included publications. A high certainty of evidence was found for the beneficial effects of liquid meal replacement on reducing body weight (mean difference −2.37 kg, 95% confidence interval −3.30 to −1.44; n=9 randomised controlled trials included in the meta-analysis) and body mass index (−0.87, −1.32 to −0.43; n=8 randomised controlled trials), and of a low carbohydrate diet (<26% of total energy) on levels of haemoglobin A1c (−0.47%, −0.60% to −0.34%; n=17 randomised controlled trials) and triglycerides (−0.30 mmol/L, −0.43 to −0.17; n=19 randomised controlled trials). A moderate certainty of evidence was found for the beneficial effects of liquid meal replacement, plant based, Mediterranean, high protein, low glycaemic index, and low carbohydrate diets (<26% total energy) on various cardiometabolic measures. The remaining results had low to very low certainty of evidence.Conclusions The evidence indicated that diet has a multifaceted role in the management of type 2 diabetes. An energy restricted diet can reduce body weight and improve cardiometabolic health. Beyond energy restriction, dietary approaches such as plant based, Mediterranean, low carbohydrate (<26% total energy), or high protein diets, and a higher intake of omega 3 fatty acids can be beneficial for cardiometabolic health in individuals with type 2 diabetes.Systematic review registration PROSPERO CRD42021252309.